Italians and Food - Sassatelli, Roberta; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book is a novel and original collection of essays on Italians and food. Food culture is central both to the way Italians perceive their national identity and to the consolidation of Italianicity in global context. More broadly, being so heavily symbolically charged, Italian foodways are an excellent vantage point from which to explore consumption and identity in the context of the commodity chain, and the global/local dialectic. The contributions from distinguished experts cover a range of topics including food and consumer practices in Italy, cultural intermediators and foodstuff narratives, traditions of production and regional variation in Italian foodways, and representation of Italianicity through food in old and new media. Although rooted in sociology, Italians and Food draws on literature from history, anthropology, semiotics and media studies, and will be of great interest to students and scholars of food studies, consumer culture, cultural sociology, and contemporary Italian studies.
Foreword: Why Italy?; Donna Gabaccia -- 1. Introduction: Food, Foodways and Italianicity; Roberta Sassatelli -- 2. The Invention of Authentic Italian Food: Narratives, Rhetoric, and Media; Fabio Parasecoli -- 3. Italians Diasporic Identities and Food; Simone Cinotto -- 4. Locating Italianicity through Food and Tourism: Playing with Geographical Scales; Chiara Rabbiosi -- 5. Food Consumption and Food Activism in Italy; Carole Counihan -- 6. Good Food and Nice People: Hospitality and the Construction of Food Quality among the Italian Middle Classes; Roberta Sassatelli and Federica Davolio -- 7. Cooks, Italianicity and the Culinary Field in Italy; Lorenzo Domaneschi -- 8. Not a Matter of Fame: Constructing the Local as Brand Value; Roberta Sassatelli and Elisa A. G. Arfini -- 9. Cookbooks and the Representation of Italian Ways of Food; Agnese Portincasa -- 10. The Carbonara-gate: Food Porn and Gastro-nationalism; Sebastiano Benasso and Luisa Stagi -- Afterword; Massimo Montanari.
Keywords: Philosophy of mind; Self; Culture; Ethnology -- Europe; Philosophy of the Self; Sociology of Culture; European Culture